2013
DOI: 10.1182/blood.v122.21.982.982
|View full text |Cite
|
Sign up to set email alerts
|

High Resource Utilizers From The Multicenter Compact Study Of Complications In Patients With Sickle Cell Disease and Utilization Of Iron Chelation Therapy

Abstract: Introduction While treating patients (pts) with sickle cell disease (SCD) can be costly, costs are not evenly distributed across pts; rather, a minority of pts accounts for a majority of costs. Identifying those pts who consume a disproportionately large share of healthcare resources can assist payers and providers in directing appropriate and targeted interventions to deliver better pt care with lower costs. The objective of this study was to understand characteristics of pts who have increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It must be clarified whether the organ damage occurs as a result of the complications where treatment is attempted by exchange transfusion, or as a result of the iron overload caused by the exchange transfusion. The pain was reported as the most frequently observed complication in all SCD patients in a multicenter cohort study, in which it was also reported that patients who received iron chelator were less likely to experience pain and other complications (24,25). Additionally, the use of sufficient iron chelation treatment in SCD patients may prevent complications and also reduce morbidity and mortality (26).…”
Section: Discussionmentioning
confidence: 99%
“…It must be clarified whether the organ damage occurs as a result of the complications where treatment is attempted by exchange transfusion, or as a result of the iron overload caused by the exchange transfusion. The pain was reported as the most frequently observed complication in all SCD patients in a multicenter cohort study, in which it was also reported that patients who received iron chelator were less likely to experience pain and other complications (24,25). Additionally, the use of sufficient iron chelation treatment in SCD patients may prevent complications and also reduce morbidity and mortality (26).…”
Section: Discussionmentioning
confidence: 99%